Suitable waves for bender element tests: Interpretations, errors and modelling aspects - Rahman, Muhammad; Pakrashi, V.; Banerjee, S.; Orr, T. (2016)
© 2016, Technical University of Budapest. All rights reserved.Extensive research on bender element tests has been carried out by many researchers, but precise guidelines for carrying out such tests have not yet been established. It is often recommended that, when using a particular bender element test for the first time on a particular soil to determine its small strain dynamic properties, several methods should be tried and the results compared in order to improve confidence in the results obtained. Demonstrated use of relatively easy analytical models for investigating different scenarios of bender element testing is another aspect that should be further looked into. This paper presents laboratory experiments and dynamic finite element analyses to determine a suitable wave for use in bender element tests in the laboratory to measure small strain shear stiffness (Gmax). The suitability of a distorted sine wave over a continuous sine wave for tests is observed from laboratory experiments and dynamic finite element analyses. The use of simple finite element models for assessing a number of aspects in relation to bender element testing is demonstrated.